Basal cell carcinoma risk and solar UV exposure in occupationally relevant anatomic sites: do histological subtype, tumor localization and Fitzpatrick phototype play a role? : a population-based case-control study - Bauer, Andrea; Diepgen, Thomas L. (Journal of occupational medicine and toxicology, 2020)
A two-fold risk increase to develop basal cell carcinoma was seen in outdoor workers exposed to high solar UV radiation compared to controls. However, there is an ongoing discussion whether histopathological subtype, tumor localization and Fitzpatrick phototype may influence the risk estimates.